THE PROFILE OF STUDENT’S SELF-ESTEEM BY THE TYPE OF STUDENT’S ACTIVITY UNIT - Devi Ratnasari; Maria Oktasari; Najlatun Naqiyah; Wiryo Nuryono (Universitas Pendidikan Indonesia, 2023)
This research was motivated by the researcher's interest in the level of self-esteem possessed by students in the student activity unit. This article aims to describe and analyze the self-esteem profile of students according to the type of student activity unit they are participating in. The research method used in this study is quantitative survey method. Data analysis was performed by testing the RASCH Model. The instrument used is a self-esteem inventory adapted from TCSEI (The Coopersmith Self-Esteem Inventory). Respondents are active students who are members of the student activity unit of Universitas Indraprasta PGRI Jakarta; Mapala Rafflesia, Japanese Zone, and Persada Choir). Samples are selected using probability sampling techniques with the type of total sampling or saturated samples. The results of the study generally show that students' self-esteem formed from the three types of student activity units is in the medium category. In particular, the results of research on the dynamics of aspects of self-esteem release different levels. In the Mapala Rafflesia student activity unit, the highest aspect is the strength aspect (which shows the ability to control behavior and obtain positive recognition), while the lowest aspect is in the significance aspect. In addition, in the Japanese Zone student activity unit, the highest aspect is the ability aspect (which is able to show high achievements and struggles, and is able to face problems) and the lowest aspect is the strength aspect. While in the student activity unit of the Persada Choir, the highest aspect is placed on the piety aspect (which identifies the ability to obey norms and ethics, and has a positive assessment of oneself), and the lowest aspect is the ability aspect. The results of this study are recommended to be used as consideration in developing guidance and counseling models related to student self-esteem.